OPTICAL COHERENCE TOMOGRAPHY CHARACTERISTICS OF MACULAR EDEMA AND HARD EXUDATES AND THEIR ASSOCIATION WITH LIPID SERUM LEVELS IN TYPE 2 DIABETES. Issue 9 (September 2016) - Davoudi, Samaneh; Papavasileiou, Evangelia; Roohipoor, Ramak; Cho, Heeyoon; Kudrimoti, Shreyas; Hancock, Heather; Hoadley, Suzanne; Andreoli, Christopher; Husain, Deeba; James, Maurice; Penman, Alan; Chen, Ching J.; et al.
Abstract : Purpose: To determine whether hyperreflective foci (HF) and macular thickness on spectral domain ocular coherence tomography are associated with lipid levels in patients with Type 2 diabetes. Methods: Two hundred and thirty-eight participants from four sites had fundus photographs and spectral domain ocular coherence tomography images graded for hard exudates and HF, respectively. Regression models were used to determine the association between serum lipid levels and 1) presence of HF and hard exudates and 2) central subfield macular thickness, central subfield macular volume, and total macular volume. Results: All patients with hard exudates on fundus photographs had corresponding HF on spectral domain ocular coherence tomography, but 57% of patients with HF on optical coherence tomography did not have hard exudates detected in their fundus photographs. Presence of HF was associated with higher total cholesterol (odds ratio = 1.13, 95% confidence interval = 1.01–1.27, P = 0.03) and higher low-density lipoprotein levels (odds ratio = 1.17, 95% confidence interval = 1.02–1.35, P = 0.02) in models adjusting for other risk factors. The total macular volume was also associated with higher total cholesterol ( P = 0.009) and triglyceride ( P = 0.02) levels after adjusting for other risk factors. Conclusion: Higher total and low-density lipoprotein cholesterol were associated with presence of HF on spectral domain ocular coherence tomography. Total macular volume was associated with higher total cholesterol and triglyceride levels. Abstract : Higher total and low-density lipoprotein cholesterol were associated with presence of hyperreflective foci on macular ocular coherence tomography in patients with Type 2 diabetes. Higher total cholesterol and triglyceride levels were associated with higher total macular volume in these patients.